PENGATURAN RETRIBUSI JASA UMUM TERHADAP PELAYANAN KESEHATAN PADA RUMAH SAKIT JIWA PROVINSI BALI - Yoga Satrya Wibawa, Gede; Arya Sumerthayasa, Putu Gede; Sarna, Kadek (Kertha Wicara : Journal Ilmu Hukum, 2013)
The arrangement of Public Service retribution collection in Bali Province is regulated in local regulation of Bali Province No. 2, 2011 concerning Public Service Retribution. The retribution is based on law No. 28, 2009 concerning local tax and retribution that serves as guideline for local government in the implementation local tax and local retribution collection. The statement of problem is about how the arrangement and implementation of health service retribution collection in Rumah Sakit Jiwa Bali Province and how the contribution of health service retribution in Rumah Sakit Jiwa Bali Province to increase provincially generated revenue in the implementation of local autonomy in Bali Province. The research method normative used to discuss those problems. In summarize that the arrangement and implementation of health service retribution collection in Rumah Sakit Jiwa Bali Province is regulated based on Local Regulation Bali Province No.2, 2011 concerning public service retribution. Moreover from reachable of reception of health service retribution shows that Rumah Sakit Jiwa Bali Province increase more than target that is planned by Bali Province Government.
Keywords: Retribution, Public Services, Health services.